Effect of Leaf Extract of Azadirachta indica (Neem Tree) on Mosquito Larvae - Bode A. S.; Adamu M. Y.; Hamawa S. S.; Gubya E. E. (African Journal of Biochemistry and Molecular Biology Research, 2026)
The larvicidal effect of neem leaf extract on early fourth-instar larvae of Anopheles gambiae was investigated under laboratory conditions of 23–30°C and 70%–75% relative humidity. Neem leaves were extracted using 70% ethanol, and the extract was evaluated at concentrations of 300, 350, 400, 450, 500, and 550 mg/L. Distilled water was used as the control. Each treatment was replicated twice, with 20 fourth-instar larvae of Anopheles gambiae exposed to each concentration and an equal number exposed to the control. The larvae were fed with Regal dried yeast during the experiment to minimize background mortality. Larval mortality was assessed after 24 hours of exposure, and the median lethal concentration was determined. The results showed that neem leaf extract exhibited larvicidal activity against Anopheles gambiae, with an LC50 value of 349.95 mg/L after 24 hours of exposure, while no mortality was recorded in the control group. The study concludes that Azadirachta indica leaf extract has potential as a plant-based biopesticide for mosquito larval control. These findings support further investigation into neem leaves and other plant parts for pesticide development and highlight the need for public education and institutional support for bio-pesticides as accessible, plant-derived alternatives for vector control.